Hepatoprotective effects of phenolic glycosides from the methanol extract of Physalis angulata - Tuan Anh, Hoang Le; Thi Dung, Duong; Tuan, Do Thanh; Hung, Trieu Quy; Hai Yen, Pham Thi; Quang, Tran Hong; Nhiem, Nguyen Xuan; Minh, Chau Van; Hai Yen, Duong Thi; Kiem, Phan Van (Vietnam Journal of Science and Technology, 2017)
By various chromatographic separations, four phenolic glycosides, methyl salicylate 2-O-triglycoside (1), icariside E5 (2), quercetin 3-O-rutinoside (3), and isorhamnetin 3-O-rutinoside (4) were isolated from the methanol extract of the whole plant of Physalis angulata. Their structures were determined by 1D-, 2D-NMR spectroscopic analyses and in comparison with the reported data. Compounds 3 exhibited significantly hepatoprotective activity with an EC50 value of 17.08 µg/mL. This is the first report of 1-4 from Physalis angulata.